Effect of feed restriction on nutrient utilization, growth and metabolic profile in crossbred calves - OJHA, B K; DUTTA, NARAYAN; PATTANAIK, A (The Indian Journal of Animal Sciences, 2018)
Present study elucidated the effect of feed restriction on growth, nutrient utilizationand metabolic profile in crossbred calves. Eighteen crossbred male calves (Bos Taurus x Bos indicus) of about 4–6 months age and 85.7±5.6 kg body weight were randomly divided into 3 groups (Control, T–15 and T-30) of 6 each in completely randomised design. The calves in control group were fed ad libitum as per predicted requirement; while in group T-15 and T-30 calves were fed 15 and 30% restricted diets of predicted requirements. Daily intake of DM and OM was significantly (P<0.05) higher in control group relative to T-30, however, T-15 had an intermediate position. Digestibility coefficient of DM and OM was significantly (P<0.01) higher in T-30 group as compared to control and T-15 groups. Efficiency of N-utilization was better (P<0.01) in T-30 and T-15 groups than control. BW gain (kg) and average daily gain (ADG; g) were significantly (P<0.01) higher in control and T-15 groups as compared to T-30. Feed conversion ratio (FCR) of calves was better (P<0.01) in T-15 as compared to T-30. Haematological parameters and serum enzymes did not differ significantly (P>0.05) among treatment groups. However, serum glucose, total protein, albumin and serum urea were found to be significantly (P<0.01) lower in T-30. Present study concluded that dietary restriction at 15% level was efficient and at par with the control group having no feed restriction.